Dulaglutide and cardiovascular and heart failure outcomes in patients with and without heart failure: a post‐hoc analysis from the REWIND randomized trial. (20th September 2022) - Branch, Kelley R.H.; Dagenais, Gilles R.; Avezum, Alvaro; Basile, Jan; Conget, Ignacio; Cushman, William C.; Jansky, Petr; Lakshmanan, Mark; Lanas, Fernando; Leiter, Lawrence A.; Pais, Prem; Pogosova, Nana; et al.
Abstract: Aims: People with diabetes are at high risk for cardiovascular events including heart failure (HF). We examined the effect of the glucagon‐like peptide 1 agonist dulaglutide on incident HF events and other cardiovascular outcomes in those with or without prior HF in the randomized placebo‐controlled Researching Cardiovascular Events with a Weekly Incretin in Diabetes (REWIND) trial. Methods and results: The REWIND major adverse cardiovascular event (MACE) outcome was the first occurrence of a composite endpoint of non‐fatal myocardial infarction, non‐fatal stroke, or death from cardiovascular causes (including unknown causes). In this post‐hoc analysis, a HF event was defined as an adjudication‐confirmed hospitalization or urgent evaluation for HF. Of the 9901 participants studied over a median follow‐up of 5.4 years, 213/4949 (4.3%) randomly assigned to dulaglutide and 226/4952 (4.6%) participants assigned to placebo experienced a HF event (hazard ratio [HR] 0.93, 95% confidence interval [CI] 0.77–1.12; p  = 0.456). In the 853 (8.6%) participants with HF at baseline, there was no change in either MACE or HF events with dulaglutide as compared to participants without HF ( p  = 0.44 and 0.19 for interaction, respectively). Combined cardiovascular death and HF events were marginally reduced with dulaglutide compared to placebo (HR 0.88, 95% CI 0.78–1.00; p  = 0.050) but unchanged in patients with and without HF at baseline ( p  = 0.31). Conclusions: Dulaglutide was not associated with a reduction in HF events in patients with type 2 diabetes regardless of baseline HF status over 5.4 years of follow‐up.